2018
DOI: 10.2147/ijgm.s165659
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practice of dry powder inhalation among patients with chronic obstructive pulmonary disease in a regional hospital, Nepal

Abstract: PurposeDry powder inhalation is a cornerstone of treatment in patients with COPD. This study was undertaken to study the knowledge and practice of dry powder inhalation among such patients.Patients and methodsThe current study was a cross-sectional study conducted in Western Regional Hospital, Pokhara, Nepal. The study was conducted among 204 COPD patients (outpatients and inpatients) aged ≥20 years who had been using rotahaler, a dry powder inhaler device, and a purposive sampling technique was used. Data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…While choosing the right device for their COPD patients, most physicians relied on pMDIs with or without a spacer. While many of these choices can be attributed to the availability of certain drugs and their combinations in specific inhalation devices, we and many of the doctors in the region believe that there is a high inspiratory flow required to activate the DPI device, which is very difficult for a patient with COPD to generate [ 5 , 7 , 13 ]. For some patients, many physicians preferred home nebulisation with SABA and SAMA combinations.…”
Section: Discussionmentioning
confidence: 99%
“…While choosing the right device for their COPD patients, most physicians relied on pMDIs with or without a spacer. While many of these choices can be attributed to the availability of certain drugs and their combinations in specific inhalation devices, we and many of the doctors in the region believe that there is a high inspiratory flow required to activate the DPI device, which is very difficult for a patient with COPD to generate [ 5 , 7 , 13 ]. For some patients, many physicians preferred home nebulisation with SABA and SAMA combinations.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported poor inhaler technique is present in up to twothirds of patients with COPD. [25][26][27][28][29] Experience in our COPD clinic past 10 years indicates that the prevalence of poor inhaler technique is well above 90% regardless of socioeconomic and/or educational background. Repeated and dedicated education is required to make clinically significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 128 potentially relevant records identified in the initial search, 12 studies were deemed eligible for qualitative and quantitative syntheses. Data obtained from 5724 asthmatic patients and 847 COPD patients were extracted from 11 observational crosssectional studies [51][52][53][54][55][56][57][58][59][60][61] and 1 RCT [31]. The study by Harb et al [31] was interventional and randomized in design; however, the error frequency in inhaler technique was assessed at baseline, prior to verbal and demonstrative instructions on correct performance.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The investigated inhaler devices included DPI (Aerolizer, Accuhaler, Breezhaler, Diskhaler, Diskus, Easyhaler, Ellipta, Genuair, HandiHaler, Rotahaler, and Turbuhaler), MDI or pressurized MDI (pMDI) with or without a spacer (such as Ventolin, Atrovent, or Combivent), and SMI (Respimat). The inhaler technique was evaluated for DPI in 11 studies [31,51,[53][54][55][56][57][58][59][60][61], for MDI in 8 studies [31,[51][52][53]55,56,58,60], and for SMI in 2 studies [31,55]. Data on bronchoreversibility were not reported in Table 1 as none of the analyzed studies included this information.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation